REPUTASI KAP, PERGANTIAN AUDITOR, DAN HAL AUDIT UTAMA TERHADAP AUDIT REPORT LAG: UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERASI (Studi Empiris pada Perusahaan Energy yang Terdaftar di Bursa Efek Indonesia Tahun 2022-2024) - Carissa Maharani; Anis Chariri (Diponegoro Journal of Accounting, 2025)
This study aims to examine the effect of Accounting Firm reputation, auditor switching, and the number of Key Audit Matters (KAM) on audit report lag, as well as the moderating role of firm size in these relationships. The dependent variable in this research is audit report lag, while the independent variables include Accounting Firm reputation, auditor switching, and the number of KAM. Firm size is examined as a moderating variable to assess whether it strengthens or weakens the relationships between the independent variables and audit report lag.The sample consists of 167 observations from energy sector companies listed on the Indonesia Stock Exchange (IDX) during the period of 2022 to 2024, selected using a purposive sampling method based on predetermined criteria. This study employs a quantitative approach, using multiple linear regression and Moderated Regression Analysis (MRA) with SPSS version 26.The results show that Accounting Firm reputation has a significant negative effect on audit report lag. Auditor switching has a positive but statistically insignificant effect, while the number of KAM also has a negative but insignificant effect. Furthermore, firm size weakens the effect of Accounting Firm reputation and the number of KAM, and strengthens the effect of auditor switching on audit report lag, although these moderating effects are not statistically significant